npj Breast Cancer - Norton, Larry; Szallasi, Zoltan; Badve, Sunil; Chandarlapaty, Sarat; Badve, Sunil; Chandarlapaty, Sarat; Norton, Larry; Szallasi, Zoltan; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Breast Cancer considers research that explores all aspects of biology and medicine relevant to breast cancer. The journal covers a broad range of topics including but not limited to: Molecular classification of disease Clinical trials and clinical research Immunotherapy and other treatments Carcinogenesis and hereditary susceptibility Molecular epidemiology Screening and disease prevention Survivorship issues Mechanisms of metastasis Tumor microenvironment studies Breast cancer imaging Mechanism-based therapies targeting signal transduction pathways Biophysics of breast cancer The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by breast cancer experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Medicine$1 (BResearch.s; Biology$1 (BResearch.s; Cancer; Oncology; Medical genetics; Cytology; Biomedical Research; Cancer Biology; Oncology; Medical Genetics; Cell Biology